A glimpse into social perception in light of vitality forms - Qingming Liu; Qingming Liu; Jinxin Zhang; Da Dong; Da Dong; Wei Chen; Wei Chen; Wei Chen (Frontiers in Psychology, 2022)
The American psychoanalyst and developmental psychologist Daniel Stern’s idea of vitality forms might suggest a new solution to explain how other minds are intensely expressed in their actions. Vitality forms characterize the expressive style of actions. The effective perception of vitality forms allows people to recognize the affective states and intentions of others in their actions, and could even open the possibility of properties of objects that are indicated by the given actions. Currently, neurophysiological studies present that there might be a neural mirror mechanism in the dorso-central insula (DCI), middle cingulate cortex (MCC), and other related cerebral areas, which serve to preferably perceive and deliver vitality forms of actions. In this article, possible types of vitality forms related to other minds, which have been brought to particular attention in recent years, have been collected and discussed in the following four areas: (1) Vitality forms on understanding non-verbal intention, (2) on understanding verbal intention, (3) vitality forms as grounding social cognition, and (4) as grounding social emotion. These four areas, however, might refer to an entirety of a binary actor-observer communicative landscape. In this review, we try to simplify the analysis by relying on two fundamental dimensions of criteria: first, the idea of vitality forms is conceived as the most basic way of observing subsequent higher-order dimensions of action, that is, understanding intention in the style of action. Thus, in the first two subsections, the relationships between vitality forms and their roles in understanding non-verbal and verbal intention have been discussed. Second, vitality forms could also be conceived as background conditions of all the other mental categories, that is, vitality forms can ground cognition and emotion in a social context. In the second dimension, the existence of social cognition or emotion depends on the existence of the stylistic kinematics of action. A grounding relation is used to distinguish a ground, that is, vitality forms, and its grounded mental categories. As relating with the domain of social perception, in this review, it has been discussed vitality forms possibly could ground social cognition and social emotion, respectively.